The Role of Intravitreal Anti-VEGF Agents in Rabbit Eye Model of Open-Globe Injury. (16th April 2021) - Zhao, Xiao; Han, Han; Song, Yinting; Du, Mei; Liao, Mengyu; Dong, Xue; Wang, Xiaohong; Kuhn, Ferenc; Hoskin, Annette; Xu, Heping; Yan, Hua
Abstract : Purpose . To evaluate the effects of intravitreal anti-VEGF agents in a rabbit model of open-globe injury (OGI). Methods . OGI was induced in the right eyes of 75 Belgian rabbits by making 5 mm circumferential incision placed 6 mm behind the limbus. The rabbits were divided into 4 groups: control ( n  = 5), OGI group ( n  = 40), and intravitreal Ranibizumab and Conbercept ( n  = 15 each). Ranibizumab or Conbercept was injected into the vitreous at 0.5 hours, 3 days, or 7 days. Vitreous fluid was collected, and levels of growth factors and cytokines were measured by enzyme-linked immunosorbent assay (ELISA). On day 28 after OGI, B scan examination and histological examination were performed to evaluate intravitreal proliferation and formation of epiretinal fibrosis. Results . Vitreous levels of vascular endothelial growth factor (VEGF), platelet-derived growth factor (PDGF), transforming growth factor-beta (TGF- β ), and plasminogen activator inhibitor-1 (PAI-1) were significantly increased in rabbit eyes after OGI. Compared to eyes in OGI group, anti-VEGF treatments significantly reduced these growth factors and cytokines. Among the 7 eyes examined from each group for intravitreal proliferative changes, they were found in 7 of 7 (100%) in OGI group and were decreased by Ranibizumab and Conbercept to 5 of 7 (71.4%) and 4 of 7 (57.1%), respectively. Both Ranibizumab and Conbercept inhibited epiretinal scar formation at the wound site, with Conbercept showing the greatest effect (maximal length of scar ( L ), L OGI  = 503 ± 82.44  μ m, L Ranibizumab  = 355 ± 43.66  μ m, and L Conbercept  = 250.33 ± 36.02  μ m). Conclusion . Anti-VEGF treatments after OGI significantly attenuated the upregulation of growth factors and cytokines in the vitreous and prevented intravitreal proliferation and epiretinal scar formation and thus may protect against the development of posttraumatic complications such as proliferative vitreoretinopathy (PVR).